PERAN KEPALA SEKOLAH DAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENGEMBANGKAN KARAKTER PESERTA DIDIK DI SMP NEGERI 1 LEMPUING JAYA - AHMAD; Nurul Hidayati Murtafiah2; Sri lestari (UNISAN JURNAL, 2022)
The success of a school depends on the quality of the principal’s supervision. The role of PAI teachers includes being responsible for the education of students, including character education. Character is a collection of values ​​that underlie attitudes and behavior that can basically be changed and changed through education, guidance and exemplary. The principal as a supervisor has played an active role in developing the character of students, including PAI teachers. However, in reality the character of students has not met expectations and has not shown significant development. It is proven by the number of students who do not go to school without information. The formulation of the problem in this study is how the role of the principal as a supervisor and PAI teacher in developing the character of students. The purpose of the study was to determine the role of school principals as supervisors and PAI teachers in developing the character of students at SMP Negeri 1 Lemembu Jaya. This study uses a qualitative method using the principal and PAI teachers as primary data sources and students and research supporting documents as secondary data. The data collection used is interviews, observation and documentation. Data analysis was carried out through data reduction procedures, data presentation and data verification and drawing conclusions. Based on the results of the study, it is known that the role of the head of SMP Negeri 1 Lemembu Jaya as a supervisor is that the principal has a class supervision program, supervision of extracurricular activities, counseling guidance, examination supervision, and utilizing the results of supervision to improve teacher or employee performance. In an effort to create the character of students, the principal makes breakthroughs by making a lesson schedule by determining the second break time along with the Dhuhur prayer time, all students are required to wear long clothes, both male and female. The role of the Religion Teacher as a Advisor is to guide students in carrying out congregational prayers and reading the Qur’an before the first hour begins assisted by other teachers, guiding students in religious activities, including PHBI activities, guiding students in social activities , such as natural disasters. The role of PAI teachers as role models, namely religion teachers at SMP Negeri 1 Lemembu Jaya, has set a good example for students. Among the examples he exemplifies are dressing in a neat uniform, speaking softly at every opportunity, both at school and outside of school. Keywords: Principal, Teacher, Character